Path Analysis Association between Domestic Violence, Anxiety, Depression and Perceived Stress in Mothers and Children’s Development - VAMEGHI, Roshanak; AMIR ALI AKBARI, Sedigheh; SAJEDI, Firoozeh; SAJJADI, Homeira; ALAVI MAJD, Hamid (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Vameghi R, Amir Ali Akbari S, Sajedi F, sajjadi H, Alavi Majd H. Path Analysis Association between Domestic Violence, Anxiety, Depression and Perceived Stress in Mothers and Children’s Development. Iran J Child Neurol. Autumn 2016; 10(4):36-48. Abstract Objective Given that several factors involved in the incidence or exacerbation of developmental disorders in children, the present study aimed to investigate the relationship between some of the risk factors affecting mothers’ health and development in children using path analysis. Materials & Methods The present cross-sectional analytical study was conducted on 750 mothers and their children in health centers in Tehran, Iran in 2014 enrolled through multi-stage random sampling. Data were collected using a demographic and personal information questionnaire, the Perceived Stress Scale, Beck’s depression Inventory, Spielberger’ anxiety inventory, the WHO domestic violence questionnaire and an ages & stages questionnaire for assessing children’s development. Data were analyzed using SPSS.19 (Chicago, IL, USA) and Lisrel 8.8. Results Developmental delay was observed in 12.1% of the children. The mean stress score was 23.94±8.62 in the mothers, 50.7% of whom showed mild to severe depression, 84.2% moderate to severe anxiety and 35.3% had been subjected to domestic violence. The path analysis showed that children’s development was affected directly by perceived stress (β=-0.09) and depression (β=-0.17) and indirectly by domestic violence (β=-0.05278) and anxiety (β=-0.0357). Of all the variables examined, depression had the biggest influence on development in the children (β=-0.17). The proposed model showed a good fit (GFI=1, RMSEA=0.034). Conclusion Children’s development was influenced indirectly by domestic violence and anxiety and directly by perceived stress and depression in mothers. It is thus suggested that more concern and attention be paid to women’s mental health and the domestic violence they experience. References 1. R. de Moura D, Costa JC, Santos IS, D. Barros AJ, Matijasevich A, Halpern R, and et al. Risk factors for suspected developmental delay at age 2 years in a Brazilian birth cohort. Paediatr Perinat Epidemiol 2010; 24(3): 211–221. 2. Karimzadeh P, Kuimarsi A, Yousefi M. A Survey of Pediatrics Resident Knowledge of Growth & Development. Iran J Child Neurol 2011; 5(2):11-16. 3. Baker R. Pediatric Primary Care Well-Child Care. USA. Lippincott Williams and Wilkins Publish. 2001. 4. Sachdeva S, Amir A, Alam S, Khan Z, Khalique N, Ansari MA. Global developmental delay and its determinants among urban infants and toddlers: a cross sectional study. Indian J Pediatr 2010; 77(9):975-80. 5. Natale JE, Joseph JG, Bergen R, Thulasiraj RD, Rahmathullah L. Prevalence of childhood disability in a southern Indian city: independent effect of small differences in social status. Int J Epidemiol 1992; 21(2):367–72. 6. Bello AI, Quartey JN, Appiah LA. Screening for developmental delay among children attending a rural community welfare clinic in Ghana. BMC Pediatr 2013; 13: 119. 7. Pradilla AG, VesgaAB, Leon-Sarmiento FE. [National neuroepidemiological study in Colombia (EPINEURO)]. Rev Panam Salud Publica 2003; 14(2):104–11. 8. Guimarães AF, Carvalho DV, Machado NÁ, Baptista RA, Lemos SM. Risk of developmental delay of children aged between two and 24 months and its association with the quality of family stimulus. Rev Paul Pediatr 2013; 31(4):452-8. 9. To T, Guttmann A, Dick PT, Rosenfield JD, Parkin PC, Tassoudji M and et al. Risk markers for poor developmental attainment in young children: results from a longitudinal national survey. Arch Pediatr Adolesc Med 2004; 158(7):643–9. 10. Earls MF, Hay SS. Setting the stage for success: implementation of developmental and behavioural screening and surveillance in primary care practicethe North Carolina Assuring Better Child Health and Development (ABCD) project. Pediatrics 2006; 118(1):e183–e188. 11. Simpson GA, ColpeL, Greenspan S. Measuring functional developmental delay in infants and young children: prevalence rates from the NHIS-D. Paediatr Perinat Epidemiol 2003; 17(1):68–80. 12. Sajedi F, Vameghi R, Kraskian Mujembari A. Prevalence of undetected developmental delays in Iranian children. Child Care Health Dev 2014; 40(3):379-88. 13. Vameghi R, Amir Ali Akbari S, Sajjadi H, Sajedi F, Alavimajd H. Correlation between mothers’ depression and developmental delay in infants aged 6-18 months. Glob J Health Sci 2015; 23; 8(5):50060. 14. Shahshahani S, Vameghi R, Azari N, Sajedi F, KazemnejadA.Validity and Reliability Determination of Denver Developmental Screening Test-II in 0-6 Year-Olds in Tehran. Iran J Pediatr 2010; 20(3):313-22. 15. Yaghini O, Danesh F, Mahmoudian T, Beigi B. Evaluation of developmental delay in infants who came in for 6th month vaccination in Isfahan city health centers. Iran J Child Neurol 2012; 6(2): 29-32. 16. Shahshahani S, Vameghi R, Azari N, Sajedi F, Kazemnejad A. Comparing the results of developmental screening of 4-60 months old children in Tehran using ASQ & PDQ. Iran Rehab J 2011; 9 (S1):3-7. 17. Ali SS.A brief review of risk-factors for growth and developmental delay among preschool children in developing countries. Adv Biomed Res 2013; 2:91. 18. Cheng ER, Poehlmann-Tynan J, Mullahy J, Witt WP. Cumulative social risk exposure, infant birth weight, and cognitive delay in infancy. Acad Pediatr 2014; 14(6):581-8. 19. Petterson S M, Albers A.Effects of poverty and maternal depression on early child development. Child Development 2001; 72(6).1794-1813. 20. Ordway M R. Depressed mothers as informants on child behavior: Methodological Issues. Res Nurs Health 2011; 34(6): 520–532. 21. Ali NS, Mahmud S, Khan A, Ali BS. Impact of postpartum anxiety and depression on child’s mental development from two peri-urban communities of Karachi, Pakistan: a quasi-experimental study. BMC Psychiatry 2013; 13:274. 22. Ahlfs-Dunn SM, Huth-Bocks AC. Intimate partner violence and infant socioemotional development: the moderating effects of maternal trauma symptoms. Infant Ment Health J 2014;35(4):322-35. 23. O’Connor TG, Heron J, Glover V: Antenatal anxiety predicts child behavioral/emotional problems independently of postnatal depression. J Am Acad Child Adolesc Psychiatry 2002, 41(12):1470-1477. 24. Murray L, Cooper PJ: Effects of postnatal depression on infant development. Arch Dis Child 1997; 77(2):99-101. 25. Latendresse G. The interaction between chronic stress and pregnancy: preterm birth from a biobehavioral perspective. J Midwifery Womens Health 2009;54(1):8-17. 26. Herring S, Gray K, Taffe J, Tonge B, Sweeney D, Einfeld S. Behavior and emotional problems in toddlers with pervasive developmental disorders and developmental delay: associations with parental mental health and family functioning. J Intellect Disabil Res 2006; 50(12):874-882. 27. Van den Bergh BR, Mulder EJ, Mennes M, Glover V. Antenatal maternal anxiety and stress and the neurobehavioural development of the fetus and child: links and possible mechanisms. A review. Neurosci Biobehav Rev 2005; 29(2):237-58. 28. Berg-Nielsen TS, Vika A, Dahl AA. When adolescents disagree with their mothers: CBCL–YSR discrepancies related to maternal depression & adolescent self-esteem. Child Care Health Dev 2003; 29(3):207-213. 29. Propper C, Rigg J. Socio-Economic Status and Child Behaviour: Evidence from a contemporary UK cohort. Centre for Analysis of Social Exclusion (CASE/125).2007. London School of Economics. http://sticerd.lse.ac.uk/case. 30. Allison SJ, Stafford J, Anumba DO. The effect of stress and anxiety associated with maternal prenatal diagnosis on feto-maternal attachment. BMC Women’s Health 2011; 11:33. 31. O’Connor TG, Heron J, Golding J, Beveridge M, Glover V. Maternal antenatal anxiety and children’s behavioural/emotional problems at 4 years: Report from the Avon Longitudinal Study of Parents and Children. Br J Psychiatry 2002; 180:502-508. 32. Brouwors Evelien PM, Baar AnneloesLVan, Pop victor JM. Maternal anxiety during pregnancy and subsequent infant development. Infant Behav Develop 2001; 24(1): 95-106. 33. Dolatian M, Hesami K, Shams J, Alavi Majd H. Relationship between violence during pregnancy and postpartum depression. Iran Red Crescent Med J 2010;12(4):377-383. 34. Ali AA, Yassin K, Omer R. Domestic violence against women in Eastern Sudan. BMC Public Health 2014; 14:1136. 35. Adeodato VG, CarvalhoRdos R, de Siqueira VR, de Matos e Souza FG. Quality of life and depression in women abused by their partners. Rev Saude Publica 2005; 39(1):108-13. 36. Malta LA, McDonald SW, Hegadoren KM, Weller CA, Tough SC. Influence of interpersonal violence on maternal anxiety, depression, stress and parenting morale in the early postpartum: a community based pregnancy cohort study. BMC Pregnancy Childbirth 2012; 12:153. 37. Forouzan AS, Dejman M, Eftekhari Baradaran M. Direct costs assault against women in Forensic Medicine in Tehran city. Payesh 2006; 5(3):201-206 (Persian). 38. Greeson MR, Kennedy AC, Bybee DI, Beeble M, Adams AE, Sullivan C. Beyond deficits: intimate partner violence, maternal parenting, and child behavior over time. Am J Community Psychol 2014; 54(1-2):46-58. 39. Holmes MR. Aggressive behavior of children exposed to intimate partner violence: an examination of maternal mental health, maternal warmth and child maltreatment. Child Abuse Negl 2013; 37(8):520-30. 40. Vameghi R, Sajedi F, Kraskian Mojembari A, Habiollahi A, Lornezhad HR, Delavar B. Cross-Cultural adaptation, validation and standardization of ages and stages questionnaire (ASQ) in Iranian Children. Iran J Public Health 2013; 42(5), 522-528. 41. Glascoe FP. Screening for developmental and behavioral problems. Mental Retard Dev Disabil Res Rev 2005; 11(3): 173–179. 42. Ahsan S, Murphy G, Kealy S, Sharif F. Current developmental surveillance: is it time for change? Irish Med J 2008; 101(4):110-2. 43. Earls MF, Hay SS. Setting the stage for success: implementation of developmental and behavioral screening and surveillance in primary care practice–the North Carolina Assuring Better Child Health and Development (ABCD) Project. Pediatrics 2006; 118 (1):e183-e188. 44. Cohen S, Kamarck T, Mermelstein R. A global measure of perceived stress. J Health Soc Behav 1983; 24(4):385-96. 45. Bastani F, Rahmatnejad L, Jahdi F, Haghani H. Breastfeeding self-efficacy and perceived stress in primiparous mothers. Iran J Nurs 2008; 21(54):9-24.(Persian) 46. Mirabzadeh A, Dolatian M, Forouzan A S, Sajjadi H, AlaviMajd H, Mahmoodi Z. Path Analysis Associations Between Perceived Social Support, Stressful Life Events and Other Psychosocial Risk Factors During Pregnancy and Preterm Delivery. Iran Red Crescent Med J 2013; 15(6): 507- 14. 47. Mohammadi Yeganeh L, Bastani F, Feizi Z, AgilarVafaie M, HaghaniH. The Effect of stress management training on mood and perceived stress in women consuming contraceptive pills. Iran J Nurs 2008; 21(53): 63-73. (Persian) 48. MomeniJavid F, Simbar M, Dolatian M, AlaviMajd H. Comparison of Pregnancy Self-Care, Perceived Social Support and Perceived Stress of Women with Gestational Diabetes and Healthy Pregnant Women. Iran J Endocrinol Metabol 2014; 16(3):156-164. (Persian). 49. Mazloom RS, Darban F,Vaghei S, Modaresgharavi M, Kashanilotfabadi M, Shad M. The effect of Stress Inoculation Program (SIP) on nurses’ Perceived stress in psychiatric wards. Evidence Based Care 2012; 2: 42-54. (Persian) 50. Bech P, Gormsen L, Loldrup D, Lunde M.The clinical effect of clomipramine in chronic idiopathic pain disorder revisited using the Spielberger State Anxiety Symptom Scale (SSASS) as outcome scale. J Affect Disord 2009; 119 (1): 43-51. 51. Court H, Greenland K, Margrain T. Measuring Patient Anxiety in Primary Care: Rasch Analysis of the 6-item Spielberger State Anxiety Scale. Value Health 2010;13(6):813-819. 52. Nasiri Amiri F. Salmalian H, Hajiahmadi M. Association between prenatal anxiety and spontaneous preterm birth. JBUMS 2009; 11 (4); 42-48.(Persian) 53. Zhang J, Gao Q. Validation of the trait anxiety scale for state-trait anxiety inventory in suicide victims and living controls of Chinese rural youths. Arch Suicide Res 2012; 16(1):85-94. 54. Razavi SH, Razavi-Ratki SK, Nojomi MM, Namiranian N. Depression and general anxiety in the prisoner of war’s children: a cross sectional study. Med J Islam Repub Iran 2012; 26(4):179-84. 55. Jakšić N, Ivezić E, Jokić-Begić N, Surányi Z, StojanovićŠpehar S. Factorial and diagnostic validity of the Beck Depression Inventory-II (BDI-II) in Croatian primary health care. J Clin Psychol Med Settings 2013; 20(3):311-22. 56. Hall BJ, Hood MM, Nackers LM, Azarbad L, Ivan I, Corsica J. Confirmatory factor analysis of the Beck Depression Inventory-II inbariatric surgery candidates. Psychol Assess 2013; 25(1):294-9. 57. Hajian S, Vakilian K, Mirzaii Najm-abadi K, Hajian P, Jalalian M. Violence against Women by Their Intimate Partners in Shahroud in Northeastern Region of Iran. Glob J Health Sci 2014; 6(3)117-130. 58. Hooper D, Coughlan J, Mullen M. Structural equation modelling: guidelines for determining model fit. EJBRM 2008; 6 (1) 53-60. 59. Deyessa N, Berhane Y, Emmelin M, Ellsberg MC, Kullgren G, Högberg U. Joint effect of maternal depression and intimate partner violence on increased risk of child death in rural Ethiopia. Arch Dis Child 2010; 95(10):771-5. 60. Avdibegović E, Sinanović O. Consequences of domestic violence on women’s mental health in Bosnia and Herzegovina. Croat Med J 2006; 47(5):730-741. 61. Burke JG, Lee LC, O’Campo P. An exploration of maternal intimate partner violence experiences and infant general health and temperament. Matern Child Health J 2008; 12(2):172-9. 62. Milgrom J, Holt C. Early intervention to protect the mother-infant relationship following postnatal depression: study protocol for a randomized controlled trial. Trials 2014;15:385. 63. Feldman R, Granat A, Pariente C, Kanety H, Kuint J, Gilboa-Schechtman E. Maternal depression and anxiety across the postpartum year and infant social engagement, fear regulation, and stress reactivity. J Am Acad Child Adolesc Psychiatry 2009; 48(9):919-27. 64. Pawlby S, Sharp D, Hay D, O’Keane V. Postnatal depression and child outcome at 11 years: the importance of accurate diagnosis. J Affect Disord 2008;107(1-3):241-5. 65. Gutteling BM, de Weerth C, Willemsen-Swinkels SH, Huizink AC, Mulder EJ, Visser GH, et al. The effects of prenatal stress on temperament and problem behavior of 27-month-old toddlers. ESCAP 2005; 14(1):41-51. 66. Laplante DP, Brunet A, Schmitz N, Ciampi A, King S. Project Ice Storm: prenatal maternal stress affects cognitive and linguistic functioning in 5 1/2-year-old children. J Am Acad Child Adolesc Psychiatry 2008; 47(9):1063-72. 67. Ciciolla L, Crnic KA, West SG. Determinants of Change in Maternal Sensitivity: Contributions of Context, Temperament, and Developmental Risk. Parent Sci Pract 2013; 13(3):178-195. 68. Ramchandani PG, Richter LM, Norris SA, Stein A. Maternal prenatal stress and later child behavioral problems in an urban South African setting. J Am Acad Child Adolesc Psychiatry 2010; 49(3):239-47. 69. O’Connor TG, Heron J, Glover V. Antenatal anxiety predicts child behavioral/emotional problems independently of postnatal depression. J Am Acad Child Adolesc Psychiatry 2002; 41(12):1470-7. 70. Tang, E, Luyten P, Casalin S, Vliegen N. Parental Personality, Relationship Stress, and Child Development: A Stress Generation Perspective. Inf Child Dev 2015;25(2):179-197.